Diseño del sistema de buenas prácticas de manufactura para la línea bovinos del centro de faenamiento municipal del cantón Guamote - Apugllón Hernández, Dennys Romario (2022)
This research project aims to design a management system of good manufacturing practices based on resolution Arcsa-067-2015-GGG for the bovine line of the municipal slaughtering center of Guamote canton administered by the Municipal Government of the canton, which offers the citizens the service of slaughtering animals for slaughter. For this purpose, an initial inspection of BPM compliance was carried out, which yielded unfavorable results due to the various problems in the following sections: facilities, quality assurance, and production operations. Consequently, a good manufacturing practices manual was designed containing procedures, records, and instructions that will help to manage compliance with BPM requirements. In addition, a Hazard Analysis and Critical Control Point (HACCP) plan were developed to analyze the physical, chemical, and biological hazards associated with the beef slaughter process. This plan specifies the monitoring system, corrective actions, and control parameters for the stages of antemortem inspection, offal removal, washing, and airing of half-carcasses, which are considered critical control points (CCP). Once the BPM manual was completed, an audit was carried out where a BPM compliance of 78.07% was obtained, considering the design of the good manufacturing practices system as a fundamental step to ensure the safety of the half bovine carcasses of the municipal slaughtering center of Guamote canton.